Ultrasound diagnosis of breast cancer - Zhou, Yufeng. (2013)
Ultrasound is a popular imaging modality for its safety and low cost. Its role in the diagnosis of breast cancer is discussed, and its performance is then compared to those of mammography (gold standard) and MRI. Besides conventional B-mode and color or power Doppler ultrasound images, latest development of acoustic radiation force impulse (ARFI) and supersonic shear imaging and their application in breast diagnosis are introduced.